Thinking international relations differently - Blaney, David L.; Tickner, Arlene B. , 1964- (Worlding beyond the West, 2012)
The discipline of international relations (IR) is ironically not at all international. This book illustrates the diversity and variation in IR around the world. It adopts a thematic structure in which four of the central concerns in IR - the state, security, globalization and secularism/religion